Pengaruh Harga dan Kualitas Produk Terhadap Keputusan Pembelian di Alfamidi Wonomulyo - Purnama; Andi Hendra Syam; Yusram Adi (Jurnal Online Manajemen ELPEI, 2023)
This research was conducted to determine the effect of price and product quality on purchasing decisions at Alfamidi wonomulyo. The population in this study were all consumers who shopped or made purchases at Alfamidi wonomulyo by calculating the population taken three months during the study, totaling 9,000 people, determining the sample in the study this uses the slovin formula so that the results of the number of samples used in this study are 99 respondents to answer the distribution of questionnaires distributed by researchers. The results of multiple linear regression analysis show that price has a positive and significant effect on purchasing decisions at Alfamidi wonomulyo, product quality has a positive and significant effect on purchasing decisions at Alfamidi wonomulyo, and price and product quality simultaneously influence purchasing decisions at Alfamidi wonomulyo. In the price variable, it is hoped that the company can increase the affordability of prices to each consumer in order to make it easier for consumers to make a purchasing decision at Alfamidi so that it benefits a company.